Recent advances of RAF (rapidly accelerated fibrosarcoma) inhibitors as anti-cancer agents - Ammar, Usama M.; Abdel-Maksoud, Mohammed S.; Oh, Chang-Hyun (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2018)
Frequent oncogenic mutations have been identified in MAPK (mitogen-activated protein kinase) signaling pathway components. As a result, MAPK pathway is associated with human cancer initiation, in particular RAF (rapidly accelerated fibrosarcoma) component. The mutation in RAF component leads to auto-activation of MAPK signaling pathway, stimulating the uncontrolled cell growth and proliferation. In last few years, diverse chemical scaffolds have been identified as RAF inhibitors. Most of these scaffolds show potent anti-cancer activity. The present review highlights the recent investigations of RAF inhibitors during the last five years. (C) 2018 Published by Elsevier Masson SAS.
Keywords: LUNG-CANCER CELLS; ACTIVATED PROTEIN-KINASE; SPECTRUM ANTIPROLIFERATIVE ACTIVITY; POTENTIAL ANTITUMOR AGENTS; DIARYL UREA DERIVATIVES; BRAF V600E MUTATION; B-RAF; BIOLOGICAL EVALUATION; PYRAZOLINE DERIVATIVES; PHARMACOPHORE APPROACH